2013
DOI: 10.1103/physrevb.87.174512
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity induced by electron doping in La1xMxOBiS2(et al.

Abstract: We report a strategy to induce superconductivity in the BiS2-based compound LaOBiS2. Instead of substituting F for O, we increase the charge-carrier density (electron dope) via substitution of tetravalent Th +4 , Hf +4 , Zr +4 , and Ti +4 for trivalent La +3 . It is found that both the LaOBiS2 and ThOBiS2 parent compounds are bad metals and that superconductivity is induced by electron doping with Tc values of up to 2.85 K. The superconducting and normal states were characterized by electrical resistivity, mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
142
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(151 citation statements)
references
References 44 publications
8
142
1
Order By: Relevance
“…First, the parent compound of the former is a semiconductor [15] while the latter is a bad metal [12]. Second, by electron doping, the resistivity decreases with the doping concentration in Sr 1−x La x FBiS 2 , which is distinct from LnO 1−x F x BiS 2 [12] and La 1−x M x OBiS 2 (M=Ti, Zr, Hf, Th) systems [32], where resistivity shows the opposite trend with the electron concentration. Third, no metal to semiconductor transition/crossover has been observed in LnO 1−x F x BiS 2 and La 1−x M x OBiS 2 systems.…”
Section: Resultsmentioning
confidence: 99%
“…First, the parent compound of the former is a semiconductor [15] while the latter is a bad metal [12]. Second, by electron doping, the resistivity decreases with the doping concentration in Sr 1−x La x FBiS 2 , which is distinct from LnO 1−x F x BiS 2 [12] and La 1−x M x OBiS 2 (M=Ti, Zr, Hf, Th) systems [32], where resistivity shows the opposite trend with the electron concentration. Third, no metal to semiconductor transition/crossover has been observed in LnO 1−x F x BiS 2 and La 1−x M x OBiS 2 systems.…”
Section: Resultsmentioning
confidence: 99%
“…The recent discovery of BiS 2 -based superconductors has triggered many research activities, because of (i) the structural similarity to cuprates and pnictides and (ii) their relatively high T c [19][20][21][22][23][24][25][26][27] . Recent theoretical calculations have suggested that a quasi-one-dimensional character of the band dispersion provides a good Fermi surface nesting [28][29][30][31][32] .…”
mentioning
confidence: 99%
“…Broadly categorising, these superconducting materials comprise the families Bi-O-S (Tc = 4.5-6 K) [1][2][3][4][5] , LnO1−xFxBiS2 (Ln = La, Ce, Pr, Nd, Sm and Yb) (Tc = 1.9-5.4 K) [6][7][8][9][10][11][12] , and Sr1−xLnxFBiS2 (Ln = La, Ce, Pr, Nd and Sm) (Tc ~ 3 K) [13][14][15][16][17] . The parent LnOBiS2 (Ln = La, Ce and Th) and SrFBiS2 compounds are semiconducting [18][19][20] . In these compounds, superconductivity is induced by doping them with suitable electron donors 6,13,16,17 .…”
Section: Introductionmentioning
confidence: 99%